Atopic dermatitis and metabolic syndrome: lifestyle or systemic inflammation?. (29th August 2019) - Vestergaard, C.
Abstract : Linked article: G. Shalom et al. J Eur Acad Dermatol Venereol 2019; 33 : 1762–1767. https://doi.org/10.1111/jdv.15642 .